Job reallocation and productivity growth in the Ukrainian transition - J. David Brown; John S. Earle (W.E. Upjohn Institute for Employment Research, 2004)
We analyze the pace and patterns of job reallocation in Ukraine using 1992-2000 panel data on nearly the surviving universe of manufacturing firms inherited from the Soviet Union. Employment growth displays substantial increase in heterogeneity during this transition period, with a corresponding rise in excess job reallocation. Unlike data for Soviet Russia in the 1980s, Ukrainian job reallocation in the 1990s was clearly productivity-enhancing, both within and across industries. The paper also estimates the effects of firm and market characteristics on the magnitude of reallocation and on the extent to which it has contributed to aggregate productivity growth.
Keywords: E24; J63; O47; P23; 330; Produktivität; Beschäftigung; Systemtransformation; Privatisierung; Ukraine